Age-related changes in synaptic markers and monocyte subsets link the cognitive decline of APPSwe/PS1 mice - Naert, Gaelle; Rivest, Serge (Frontiers in Cellular Neuroscience, 2012)
Alzheimer’s disease (AD) is characterized by a progressive memory decline and numerous pathological abnormalities, including amyloid β (Aβ) accumulation in the brain and synaptic dysfunction. Here we wanted to study whether these brain changes were associated with alteration in the population of monocyte subsets since accumulating evidence supports the concept that the innate immune system plays a role in the etiology of this disease. We then determined the immune profile together with expression of genes encoding synaptic proteins and neurotrophins in APPSwe/PS1 mice and their age-matched wild-type littermates. We found that the progressive cognitive decline and the dramatic decrease in the expression of numerous synaptic markers and neurotrophins correlated with a major defect in the subset of circulating inflammatory monocytes. Indeed the number of CX3CR1lowLy6-ChighCCR2+Gr1+ monocytes remained essentially similar between 5 weeks and 6 months of age in APPSwe/PS1 mice, while these cells significantly increased in 6 month-old wild-type littermates. Of great interest is that the onset of cognitive decline was closely associated with the accumulation of soluble Αβ, disruption of synaptic activity, alteration in the BDNF system and a defective production in the subset of CX3CR1lowLy6-ChighCCR2+Gr1+ monocytes. However, these memory impairments can be prevented or restored by boosting the monocytic production, using a short treatment of macrophage colony-stimulating factor (M-CSF). In conclusion, low CCR2+ monocyte production by the hematopoietic system may be a direct biomarker of the cognitive decline in a context of AD.